PEMBERDAYAAN GENERASI MUDA MAHASISWA DALAM PENGENALAN PRODUK LOKAL MASYARAKAT TERINTEGRASI PEMBELAJARAN KAMPUS: PEMBERDAYAAN GENERASI MUDA MAHASISWA DALAM PENGENALAN PRODUK LOKAL MASYARAKAT TERINTEGRASI PEMBELAJARAN KAMPUS - Ade Ismail; Fajar Maulana Wijaya Kusumah; Ika Yuliasari (Jurnal Kajian Budaya dan Humaniora, 2024)
Creativity and Entrepreneurship course as a course that includes a useful project as an actualization of Pancasila and Jatidiri values in an innovative and creative way. OKK students created the 'Villana' project which is taken from the words Village and Jatinangor. "Villana product Taste Adventure"; this project focuses on the introduction and promotion of village products in Jatinangor known as "Villana products". This activity aims to improve the economy of the local community, significantly increasing the sales of Villana local products in the local market. Social Action Project Plan: (a) Local Product Development and Marketing: Supporting local producers in developing and marketing Villana products such as banana-based products and ornamental plants, (b) Distribution and marketing of products through local partners. The final results are also as expected, which can help local products and promote them widely to help the economy in Jatinangor villages.